Quality assurance in analytical chemistry [compact disc] : applications in environmental, food and materials analysis, biotechnology, and medical engineering - 230460 Funk, Werner; Dammann, Vera; Donnevert, Gerhild (New York, NY : John Wiley, 2007)
42